La coordination en travail social : un avatar du management transversal - Emmanuel Triby (Éducation et Socialisation)
This contribution would like to answer a double question: how does coordination relate to management? What does all this tell us on current social work practices? The management activity is thus questioned as well as the coordination function, emerging in the field of social work, and presented as an avatar of transversal management. To answer the original question, research-training has been set up within the framework of a professionalizing university training intended for professionals in the social sector already in activity. The results of this approach above all show the extreme diversity of practices in this area in relation to the contexts crossed as much as to the career of the professionals involved. The coordination function is thus illuminated both from the point of view of the dispositions they imply among professionals and the conditions of possibility of this function. A coordination economy is emerging, providing a framework for possible shared learning, through the implementation of this management.